Enhancing cross-cultural adjustment : a case study of international researcher's spouses in Finland - Bélanger, Karelle (2019)
This thesis explores the perceived organizational support of the Hidden Gems programme in enhancing cross-cultural adjustment and employability of international researchers’ spouses experiencing career interruption in Finland. One third of Tampere University researchers are of foreign background and 40 percent of today’s researchers relocate with their spouse or partner. Previous research provides evidence that the spouses of international researchers and other university employees have, on average, higher qualification levels than other immigrant groups. Despite their qualifications, they may have to stay home for years before finding employment. Improving spousal adjustment and employment in the host country has the potential to reduce the risk of premature return of the international researchers and their spouses. Hidden Gems is a new programme offered for the Tampere University researchers’ spouses to promote the utilization of immigrant professionals’ expertise and human capital to meet the needs of industry and business, so that the participants find employment that corresponds to their qualifications and ensures them fair compensation.